The determinants of value for money in procurement of works in Tanzania’s Local Government Authorities: A case of selected LGAS in Dar es Salaam region - Nyaonge, Mbiji M. (Mzumbe University, 2024)
A Dissertation Submitted to Mzumbe University in Partial Fulfillment of the Requirements for the Award of Master Degree of Science in Procurement and Supply Chain Management of Mzumbe University, 2018